Marketing of Tourism Destination in the Context of Tiger Safari - Nilanjan Ray; Tapas Kumar Chatterjee; Subrata Kumar Mitra (ASEAN Journal on Hospitality and Tourism, 2022)
Tiger tourism plays a significant role in the overall scenario of Indian tourism. The forest destination managers face a major challenge in satisfying their visitors since tigers are elusive by nature and most of the time tourists return dissatisfied without sighting a tiger after a forest safari. This paper is the first scientific study of its kind based on empirical data in the context of tiger tourism and proposed a model to identify the optimum path in the forest with a higher probability of tiger sighting.